Impact of Awareness Campaigns on Social Health Insurance Uptake in Bayelsa State, Nigeria - Ebiakpor Bainkpo Agbedi; Pere-Ere Glory Agbedi (American Journal of Medicine and Health Care, 2026)
Social health insurance (SHI) in Bayelsa State, Nigeria, aimed to enhance healthcare access and reduce out-of-pocket expenditures through pooled financial resources. Despite the implementation of awareness campaigns to promote SHI, significant gaps in enrolment and knowledge persisted among diverse populations. This study evaluated the impact of radio, television, and stakeholder engagement campaigns on SHI enrolment decisions, perceived value, and ongoing participation. It sought to identify the reach and effectiveness of these campaigns across different geographic and demographic segments. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. A structured questionnaire was administered to a sample of 600 participants across urban, rural, riverine, upland, and coastal communities. Data collection took place through face-to-face interviews and was supplemented with stakeholder discussions to capture contextual barriers and enablers related to SHI. The findings revealed that traditional media, particularly television and radio, were the most effective channels for disseminating information about SHI, with significant engagement reported among respondents. Awareness of the financial benefits of SHI was high, with 42% recognizing its role in reducing out-of-pocket expenses. The chi-square test indicated a strong association between awareness of SHI and knowledge of eligibility criteria, while linear regression analysis confirmed that the awareness campaigns positively influenced both SHI uptake and financial protection. The study concluded that effective awareness campaigns significantly enhanced the understanding and uptake of social health insurance in Bayelsa State. It underscored the necessity for tailored communication strategies that leverage traditional media and address contextual barriers to achieve broader enrolment and sustained participation in SHI initiatives.